Economic impact of immunoglobulin replacement therapy in secondary immunodeficiency to hematological cancer: a single center observational study - Guerola, Luciana del Campo; Sacristán, Ana Andrea García; Portolés, Antonio; Jasso, Maricruz; Guerra-Galán, Teresa; de la Fuente-Munoz, Eduardo; Palacios-Ortega, María; Fernández-Arquero, Miguel; Cuesta-Mínguez, Cristina; Rodríguez-Sanz, Aránzazu; Peña-Cortijo, Ascensión; Polo, Marta; et al. (Frontiers in Immunology, 2024)
This is the first report of the health economic benefits derived from preventing infections through Immunoglobulin Replacement Therapy (IgRT) in patients with secondary immunodeficiency due to hematological malignancies. We conducted a retrospective population-based cohort study using patient medical history and pharmacy data from the Hospital Clínico San Carlos for 21 patients between 2011 and 2020. The pharmacoeconomic impact of using prophylactic IgRT was assessed by comparing characteristics of the SID patients 1 year before and after initiating IgRT measured by direct medical and tangible indirect costs. Results indicate a marked reduction in hospitalization days following IgRT initiation, decreasing from an average of 13.9 to 6.1 days per patient, with the elimination of ICU admissions. While emergency department visits decreased significantly, the number of routine consultations remained unchanged. Notably, absenteeism from work dropped substantially. The financial analysis revealed significant reductions in medication use and fewer ancillary tests, resulting in considerable cost savings. Specifically, total expenditure dropped from €405,088.18 pre-IgRT to €295,804.42 post-IgRT—including the cost of IgRT itself at €156,309.60. Overall, the annual savings amounted to €109,283.84, validating the cost-effectiveness of IgRT in managing SID in patients with hematological cancers.